Institutional Reform and Social Justice in Child Protection Systems - Widaningsih (Sinergi International Journal of Law, 2025)
This narrative review investigates the alignment between international child rights frameworks and domestic implementation practices across multiple regions, with a focus on vulnerable populations, including children in armed conflict, refugee contexts, and marginalized communities. Drawing on a systematic synthesis of empirical and theoretical literature, the study utilized databases such as Scopus, Google Scholar, JSTOR, and HeinOnline to explore the themes of child justice, education, healthcare access, and protection from violence and exploitation. Results highlight persistent challenges in translating global norms, such as the UNCRC, into actionable national policies due to bureaucratic fragmentation, cultural resistance, and political instability. Comparative insights from conflict and post-conflict countries underscore the critical role of institutional maturity, legal reform, and interagency collaboration in enhancing child protection mechanisms. The discussion further emphasizes the importance of child participation, cross-sectoral policy coherence, and community-based approaches. Legal innovations such as specialized child courts and inclusive education policies are found to be effective when combined with capacity-building and sustained monitoring systems. This review concludes that child rights protection demands a multidisciplinary and culturally sensitive strategy that integrates legal, educational, and social sectors. Future research should address existing gaps by evaluating context-specific interventions and developing scalable models that strengthen national compliance with international norms.